Heavy metals leaching behaviour assessment of palm oil clinker - Mohammad Razaul Karim,; Sumiani Yusoff,; Hashim Abdul Razak,; Faisal I. Chowdhury,; Hossain Zabed, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Technical benefit of incorporation of Palm Oil Clinker (POC) in cement-based applications has been proven in recent studies. The aim of this work was to assess the heavy metal leaching behavior to ensure environmental safety of using POC in cement-based applications. The chemical composition, morphology, total organic carbon (TOC) and mineralogy were determined using XRF, FESEM, TOC analyzers and XRD to select appropriate chemical reagents for complete digestion. HNO3, HF and HClO4 were used for digestion of POC to measure heavy metal content using ICP-MS. The chemical reagents CH3COOH, NH2OH-HCl, H2O2+CH3COONH4 and HF+HNO3+HCl were used for extraction of acid soluble, reducible, oxidizable and residual fractions of heavy metals in POC, respectively. The leaching toxicity of the POC was investigated by the USEPA 1311 TCLP method. The result showed the presence of Be, V, Cr, Ni, Cu, Zn, As, Se, Ag, Cd, Ba and Pb with levels of 5.13, 11.02, 2.65, 1.93, 45.43, 11.84, 15.07, 0, 0, 81.97 and 1.76 mg/kg, respectively, in POC. The leaching value in mg/L of As (4.56), Cu(1.05), Be (0.89), Zn(0.51), Ba(0.26), Ni (0.17), V(0.15), Cr(0.001) and Se (0.001) is found well below the standard limit of risk. Risk assessment code (RAC) analysis confirms the safe incorporation of POC in cement-based applications.